Role of Fluid Interia in Porous Material Subject to Dynamics Loadings - Kowalski, S.J.; Musielak, G. (Engineering Transactions, 1992)
The paper is aimed at analysing the dynamical properties of fluid-filled porous media in which the inertial coupling effect (due to the complexity of the pore structure) is taken into consideration. Particular attention is given to the influence of the mass coupling coefficient p12 = -Pa on the wave propagation velocities in fluid-filled porous medium, on the natural frequencies of fluid-filled porous cylinder, and on transmission of forces through such a cylinder, what is important for the determination of vibration-isolation properties of the medium.